Career Choices for Individuals with Hearing Impairment in Higher Learning Institutions in Lusaka-Zambia - Rachel Muuma Chomba; Joseph Mandyata; Kenneth Kapalu Muzata (LPPM STKIP Kusuma Negara, 2023)
This study established the facilitators and barriers to career choices for persons with hearing impairment in selected workplaces and higher institutions of learning in Lusaka, Zambia. A qualitative approach and a descriptive study design were used in the study. In-depth interviews were used to collect data from twenty (26) participants that included ten (10) students with hearing impairment, six (6) Lecturers and ten (10) individuals with Hearing Impairment. The findings revealed that there were various elements that influenced career choices and these included communication barriers which inhibited receipt of career information from providers, pre-conceived ideas of what a Hearing Impaired (HI) individual can or cannot do, unavailability of chances to show self-efficacy or determination among others. The study revealed that minimal efforts were made by higher learning institutions to enhance career choices for HI students. The study recommended that career guidance should be offered in secondary schools as a routine advancement programme for individuals with Hearing Impairment as a prerequisite to applying for admission in colleges and universities. Tertiary education institutions must provide reasonable accommodations and additional support to students with Hearing Impairment to be able to access career information.